Permasalahan Hukum Pengaturan Bank Tanah Pasca Undang-Undang Nomor 11 Tahun 2020 tentang Cipta Kerja - Wahyu Bening; Ilham Dwi Rafiqi (Jurnal Suara Hukum, 2022)
Land problems in Indonesia are increasing along with the presence of Law Number 11 of 2020 on Job Creation, one of which is the issue of Land Bank Regulations. This paper will examine how the problematics of setting up the Land Bank are, starting from institutional problems and legal issues in particular. This paper uses a normative legal research method using a statutory and conceptual approach. The results of the study indicate that the presence of the Land Bank Agency has a great potential to cause overlapping authorities between institutions in the land sector. The authority of the Land Bank Agency in the management and acquisition of land was previously also owned by the Ministry of ATR/BPN, so this causes an overlap between the two institutions. Other legal issues, relating to the orientation and substance of the Land Bank Agency. Based on the Job Creation Law, the orientation of the Land Bank is more on investment and economic development that contains risks. The problematic Land Bank arrangements in the Employment Creation Law and the Land Bank PP have the potential to conflict with the goals of agrarian reform and constitutionality in the agrarian sector.